Study of papain-cystatin interaction by intensity fading MALDI-TOF-MS - Shabab, M.; Kulkarni, Mahesh J.; Khan, Mohammad Islam (Protein Journal, 2008)
Intensity fading (IF) matrix assisted laser desorption ionization (MALDI) time of flight (TOF) mass spectrometry (MS ) has become an alternative screening approach for the affinity-binding analysis of proteins and peptides with molecular ligands. In this investigation an attempt has been made to study the protein ligand interaction by intensity fading (IF) MALDI-MS using papain and cystatin as model system for protein-ligand interactions. The intensity fading of cystatin was monitored using various concentration of cystatin ranging from (1 to 8.6 mu M) in presence of target protein, papain. The results indeed indicate that the intensity of cystatin decreases upon addition of papain. Furthermore, for the first time we have used IF-MALDI-MS for determining the number of binding sites for cystatin on papain by Scatchard analysis.
Keywords: intensity fading; MALDI; papain-cystatin; protein-ligand interaction; Scatchard plot